DESIGN OF APPLICATIONS FOR ACCESS TO DIGITAL ART WORKS IN ONLINE MUSEUMS - ZHAO, J.; YEZHOVA , O. (Art and Design, 2024)
The purpose. The research aims to explore the integration of digital art with online exhibitions in museums, focusing on the design of application interfaces and museum exhibitions. Methodology. The study uses a mixed approach that combines theoretical research, analysis of scientific research with analysis of practical examples. Results. It has been found that the use of digital art has a significant impact on museum online exhibitions, contributing to more interactive, immersive, and inclusive visitor access. The integration of ICT into the museum sector, while primarily focused on digitization, virtual tours, and increasing visitor engagement through augmented reality and virtual reality technologies, also encompasses important design aspects such as color, typography, and interface design, which play an important role in the overall design of an online museum. Examples of the Central American Museum of Art, the Dunhuang Online Museum, the Metropolitan Museum of Art, as well as the Bloomberg Connects application are analyzed. The study highlights the importance of narrative design and user-centered approaches in the design of online museums to access digital cultural heritage. The scientific novelty lies in the fact that the design principles of the interface of digital applications for visitors' access to the expositions of online museums were further developed in the work. Practical Significance. The results of the study can be implemented in the modern practice of museum design projects, contributing to innovations in the presentation of cultural heritage artifacts.